UTILIZĂRI ALE PREPOZIȚIILOR LA, DE ȘI DE LA ÎN STRUCTURI DE GENITIV SAU DE DATIV DIN ROMÂNA NONSTANDARD (Analele Universității București. Limba și literatură română, 2024)
In the present article the author describes the use of the prepositions la, de, and de la in genitive or dative structures, encountered in the regional varieties of Romanian, emphasizing the frequency of the aforementioned structures and their specific features as shown in the corpus of dialectal texts investigated.The author also illustrates and discusses the different stages of grammaticalization of the preposition la in the expression of the genitive and dative and the connection between the genitive/dative relation and the locative relation.
Keywords: functional preposition; genitive; possessive; dative; locative; nonstandard Romanian